Exploring the Impact of Omnichannel Marketing on Service Quality and Firm Performance in the Banking Sector within Society 5.0 - Anthonius S. Hutabarat; Irawan R.D Budianto; Fajri Fajri (Jurnal Ekonomi, 2024)
In an era characterized by rapid technological advancements and evolving consumer expectations, the banking sector is increasingly adopting omnichannel marketing strategies to enhance service quality and improve organizational performance. Omnichannel marketing, defined as a seamless and integrated approach to consumer engagement across multiple channels, is particularly relevant in the context of Society 5.0, a vision that aims to create a human-centered society leveraging advanced technologies such as artificial intelligence, big data, and the Internet of Things. The interplay between omnichannel marketing and Society 5.0 presents unique opportunities for banks to redefine their customer service paradigms, offering personalized experiences that meet the demands of a digitally-savvy clientele. However, the implementation of these strategies is fraught with challenges, including the need for robust technological infrastructure and the integration of diverse communication platforms, which can hinder the realization of anticipated benefits. As the banking sector seeks to measure the impact of omnichannel marketing on service quality, it becomes critical to identify the key performance metrics that reflect improvements in customer satisfaction and operational efficiency. Furthermore, existing case studies illustrate successful applications of these strategies, providing valuable insights into best practices and the tangible benefits achieved through enhanced service delivery. Looking forward, this research paper aims to explore emerging trends in omnichannel marketing within the banking sector, offering strategic recommendations for institutions to optimize their approaches in alignment with the goals of Society 5.0. By critically assessing the effects of omnichannel marketing strategies on service quality and organizational performance, this study endeavors to contribute to the ongoing discourse on the evolution of banking in a technology-driven society, ultimately equipping financial institutions with the knowledge to thrive in a competitive landscape.